Das Museum als Schauplatz reflexiver anthropologischer Situationen - Jörn Schafaff (21: Inquiries into Art, History, and the Visual, 2022)
In 1998 the Migros Museum for Contemporary Art presented Rirkrit Tiravanija’s exhibition Das soziale Kapital. Recognized by the press mostly for its participatory approach and the convivial sociability of some of the exhibition’s offerings, the show was in fact designed as a set of environments evoking diverse modes of interaction, perception and behaviour: a fully functional Migros supermarket, a car repair shop, or several works by the artist inviting visitors to play music together or share a meal. Completed by artworks from the museum’s collection, the scenery thus oscillated between art exhibition, ethnographic museum and everyday life. Drawing on some of Tiravanija’s earliest works I will therefore argue that Das soziale Kapital should be understood as a performative critique of the prevailing conventions of exhibition culture.